Organic Residues and Ammonium Effects on CO2 Emissions and Soil Quality Indicators in Limed Acid Tropical Soils - De Shorn E. Bramble; Gregory A. Gouveia; Ravindra Ramnarine (Soil Systems, 2019)
Aglime (agricultural lime), commonly applied to acid soils to increase the soil pH and productivity, may lead to the release of CO2 into the atmosphere or to carbon (C) sequestration, although the processes involved are not fully understood. As large acreages of arable land are limed annually, exploring soil management practices that reduce aglime-induced CO2 emissions from acid soils while maintaining or improving the soil quality is paramount to mitigating the effects of global climate change. This study, therefore, assessed the effects of organic residues and ammonium on CO2 emissions and soil quality indicators in two limed soils. Two contrasting acid soils (Nariva series, Mollic Fluvaquents and Piarco series, Typic Kanhaplaquults) were amended with varying combinations of aglime (0% and 0.2% w/w CaCO3), organic residue (0% and 5% w/w biochar or poultry litter), and NH4-N (0% and 0.02% w/w) and were incubated in 300 mL glass jars for 31 days. The sampling for CO2 was performed on 11 occasions over the course of the incubation, while soil sampling was conducted at the end. The results indicate that aglime application significantly (p < 0.05) increased the cumulative CO2 emissions in all cases except with the addition of poultry litter. Alternatively, ammonium did not regulate the effect of aglime on CO2 emissions, which was likely because of the low rate at which it was applied in comparison to aglime. The results also showed that poultry litter significantly (p < 0.05) increased the soil electrical conductivity (EC), available nitrogen (N), and pH, especially in the Piarco soil, while the hardwood biochar had little to no effect on the soil properties. Our findings indicate the potential for utilizing poultry litter to reduce the impact of aglime on CO2 emissions while improving the soil quality. Further studies utilizing 13C to trace aglime CO2 emissions are, however, required to identify the mechanism(s) that contributed to this reduction in the emissions.